BENEFITS OF COMPLEMENTARY THERAPY THROUGH TELEMEDICINE SUPPORT IN PALLIATIVE CARE OF BREAST CANCER: SYNERGY OF PAIN MANAGEMENT AND PSYCHOLOGICAL SUPPORT ON QUALITY OF LIFE - Khamid, Abdul; Susanti, Ida; Maulidia, Dinda Putri; Safitri, Eka Novia Noor; Nabilla, Calista Kheisha; Febrianti, Aulia Ningtias Rahma; Firmansah, Feri; Rahmadina, Alisha; Nurseha, Hasipah; Ramadhan, Elsya Ayu Mustika (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Benefits of Complementary Therapy in Palliative Care for Breast Cancer: The Synergy of Pain Management & Psychological Support for Quality of Life Breast cancer is the most generic type of cancer in women, using significant impact on the physical, psychological, and social aspects of the patient. Holistic palliative care, including complementary therapy, is serious about improving the patient's quality of life through pain management and psychological support. This study aims to evaluate the effectiveness of complementary therapies such as acupuncture, yoga, and music therapy in reducing pain and enhancing the psychological well-being of breast cancer patients. This systematic review uses PRISMA guidelines, covering studies published between 2020–2024. The results showed that complementary therapies significantly helped reduce the intensity of pain, anxiety, & depression, and improve overall quality of life. The integration of complementary approaches to palliative care can lead to.